Management Of Physiotherapy Programs In Skin Flap For Thumb : Case Report - Della Annisa Thalib; Umi Budi Rahayu; Nilam Nur Hamidah (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2024)
Skin flap is a skin graft procedure that will repair damaged skin by removing the soft tissue underneath. Objective: to determine Physiotherapy management in the form of giving electro therapy (ultrasound and Infrared) and exercise. Methods: The research method includes a "case report" case study conducted on 1 male patient with a diagnosis of Stiffness wrist digiti 1-5 manus dextra hand function disorders, ec. Amputation of fingers manus dextra post flap). The measuring instruments used are using the Numeric Rating Scale (NRS) for pain scale, Wrist Hand Disability Index (WHDI) to measure functional activity ability, Gonimeter to measure joint motion scope, Manual Muscle Testing (MMT) to measure muscle strength, mitline to measure odema segment circumference. Results: After 3 times of therapy, the patient's assessment results were obtained, namely a significant change in the level of joint scope of motion, muscle strength, skin integrity, motion pain in the wrist and fingers of the right hand, and functional ability. Conclusion: This case study shows that the administration of electrotepsy and exercises in the case of Skin Flap of the thumb of the hand, proved to be effective.